Development of Digital Student Worksheets with the Discovery Learning Model to Improve Collaboration Skills and Results for Elementary School Students: Literature Review - Rahayu, Ika Mei Puji; Nasution, Nasution; Mustaji, Mustaji (International Journal of Emerging Research and Review, 2023)
Objective: This research reviews the literature regarding the development of Digital Student Worksheets based on the discovery learning model to improve collaboration skills and student learning outcomes in elementary schools. This review article is a literature review research. Method: used is a narrative review, which consists of four stages: selecting the topic to be reviewed, selecting national journals and international journals that are relevant to the latest five years, namely 2018-2023, totaling ten articles, conducting literature analysis and synthesis, and compiling review results. Results: The results of the literature review show that e-LKPD can improve collaboration skills and improve student learning outcomes. Novelty: this research provides a new color for the literature review on e-LKPD, specifically on the discovery learning model for Natural and Social Sciences (NSS) subjects in elementary schools.